THE EFFECT OF PERCEIVED THREAT COVID-19, JOB STRESS, JOB BURNOUT ON JOB SATISFACTION AT EMPLOYEE AT INTERNATIONAL AIRPORT SOEKARNO HATTA - Yessi Gustiningtyias; Netania Emilisa (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
In this study, the aim to analyze the effect of perceived threat Covid-19, job burnout, job stress, and job satisfaction at Soekarno Hatta International Airport employees. By using purposive sampling method, totaling 100 employees as respondents of this study. The data collection method used was cross sectional. The data analysis technique used is instrument testing in the form of validity and reliability tests, as well as hypothesis testing using SEM with SPSS version 23 and Amos software. So the results show that Job Satisfaction has a positive effect on the Effect of Perceived Threat Covid-19, Job Burnout, and Job Stress. Managerial implications in this study companies can improve and maintain the comfort, well-being, and job satisfaction felt by employees in doing work